HUBUNGAN PERAN POS KESEHATAN PESANTREN DENGAN PENERAPAN PERSONAL HYGIENE SANTRI - Yuniasih, Lilis; Wibowo, Marsiana (Universitas Ahmad Dahlan, 2020)
Personal hygiene is one's effort to maintain cleanliness and health to obtain physical and psychological well-being. As many as 50% of students in Islamic boarding schools experience diseases related to personal hygiene including scabies and pediculosis capitis. Poskestren is a manifestation of community-based health efforts within the boarding school environment, with principles from, by and for pesantren residents, which prioritizes promotive and preventive services without neglecting the curative and rehabilitative arrangements with the development of local puskesmas. Thus the poskestren is one of the references in health development in Islamic boarding schools which should be able to overcome health problems. However, with the presence of the boarding school health post, diseases related to personal hygiene in Islamic Boarding School X, Bantul Regency have yet to be completely resolved. The purpose of this study was to determine the relationship between students' perceptions of the role of the boarding school health post with the personal hygiene of students in Islamic Boarding School X, Bantul Regency. This study uses an observational analytic method with a cross-sectional approach. The population of this study were all 56 students living in Islamic Boarding Schools X and the sampling technique used was total sampling. Respondents who met the criteria totalled 51 people. Data were analyzed by the Chi-square test. Statistical test results showÂ that there was a relationship between promotive efforts with the application of students personal hygiene (Ï = 0,000) and there is no relationship between preventive efforts (Ï = 1,000), curative (Ï = 1,000), and rehabilitative (0.840) with the application of santri personal hygiene. There was a relationship between perception about the role of poskestren promotive efforts with the implementation of personal hygiene of students and there was no relationship between perception of the role of health post boarding school with the application of personal hygiene of students in Boarding school Â X, Bantul Regency